Meaning Of Life’s Orientation Of High Schools Students In The City Of Zakho - Omer, Jihan H.; Mohammed, Zahid S.; Mohammed, Vaman A.; Ali, Nizar I. (Humanities Journal of University of Zakho, 2017)
The search aims to identify Meaning of life’s orientation of high schools students in the city of Zakho in general and its relationship with some social and cultural variables, and also to identify statistical differences between their view of point depending on the variables (gender, class, family economic state, family’s economic state, parents educational level, residence in town or villages, parents living). The sample of research consisted of (271) students selected in whole from the Zakho’s high schools according to random sampling method. For this purpose researchers used scale meaning of life’s which has been prepared by D. A. Leontev, consisting of (20) items, where extracted psychometric properties, and for the purpose of processing data was used appropriated statistical methods, frequency distribution, mean deviation, standard deviation, T-test, ANOVA. The results shows a positive level of life orientation among most of the students, also found there is statically significant differences according to variables of (family’s economic level and level of parents academic state) and also found there is no statically significant differences according to variables of (sex, class, students’ family residence and state of parents’ life), and in the light of the results researchers presented some recommendations and suggestions.